Sand - Howey, Hugh (London Century, 2014)
In post-apocalyptic Colorado, a state now covered in sand, one family struggles to survive and stay united after the father leaves. Wife and mother, Rose, has only a whore house and as her income dwindles, she finds she must work in the establishment she runs. Her children, Palmer, Victoria, Rob and Conner, all take on the dangerous job of being sand divers, hoping to help their mother with expenses.
Keywords: Families -- Civilization -- Survival